2010
DOI: 10.4028/www.scientific.net/kem.450.461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Residual Stresses in Additive Layer Manufacturing by Laser Melting of Metal Powders

Abstract: Determining the three-dimensional residual stress fields and the associated distortions using numerical simulations for multi-layered parts has proved to be a challenge in additive layer manufacturing. This paper presents an innovative three-dimensional thermal-elasto-plastic finite element model for predicting the deformation and residual stress fields in TiAl6V4 parts built on steel platforms. The developed model utilises temperature dependent material physical and mechanical properties as well as latent hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…According to Kruth et al (Ref 18 ), for the same energy density doubling the layer thickness reduced the curling angle of a bridge geometry by 6%. According to Roberts et al (Ref 17 ), doubling the layer thickness reduced the residual stress by 5%. According to Zaeh et al (Ref 14 ), increasing the layer thickness by 2.5 times decreased the deformation of the ends of a T-shaped cantilever by 82%.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Kruth et al (Ref 18 ), for the same energy density doubling the layer thickness reduced the curling angle of a bridge geometry by 6%. According to Roberts et al (Ref 17 ), doubling the layer thickness reduced the residual stress by 5%. According to Zaeh et al (Ref 14 ), increasing the layer thickness by 2.5 times decreased the deformation of the ends of a T-shaped cantilever by 82%.…”
Section: Introductionmentioning
confidence: 97%
“…Delgado et al (Ref 31 ) reported that increasing layer thickness had a negative effect on the mechanical properties of AISI 316L SLM components. Parts were created with different layer thicknesses using the same parameters (Ref 12 , 14 , 17 , 18 , 29 - 31 ), optimized for one layer thickness. From the published work, the effect of layer thickness on residual stress and mechanical properties is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the thermal conductivity of powder is different than the solid material, as the contact area among adjacent particles is smaller. 73 It has been proved that the effective thermal conductivity of powders is a function of multiple factors, such as particle size and shape, solid volume fraction, thermal conductivity of the solid and the thermal conductivity of the gaseous media. 74 Several studies consider constant thermal conductivities, both for the powder and the solid state, in order to reduce the complexity of the model.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…When creating products by using methods of AM, large temperature gradients and technological residual stresses arise in the volume of the material, resulting in disruption of the product shape, changes in the mechanical and operational characteristics of the object, and its destruction during manufacturing (King et al 2015;Li et al 2010;Ibiye et al 2011;Parry et al 2015;Wu et al 2014;Baufeld et al 2010;Riedlbauer et al 2012). In order to work out the regimes and optimize the technological process, it is advisable to carry out a preliminary modeling of the process of layer-by-layer formation of the product, which boils down to a multivariate solution of thermoconversion problems.…”
Section: Introductionmentioning
confidence: 99%